2014
DOI: 10.1128/aac.02800-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cefazolin versus Oxacillin for Treatment of Complicated Bacteremia Caused by Methicillin-Susceptible Staphylococcus aureus

Abstract: e Contrary to prior case reports that described occasional clinical failures with cefazolin for methicillin-susceptible Staphylococcus aureus (MSSA) infections, recent studies have demonstrated no difference in outcomes between cefazolin and antistaphylococcal penicillins for the treatment of MSSA bacteremia. While promising, these studies described low frequencies of high-inoculum infections, such as endocarditis. This retrospective study compares clinical outcomes of cefazolin versus oxacillin for complicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
76
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 26 publications
10
76
0
2
Order By: Relevance
“…Our results are consistent with those from other related recently published studies (12,16,17,27). However, in comparison to previous studies, we observed higher rates of endocarditis, in which 16.5% (17/103) of patients carrying the diagnosis of infectious endocarditis were treated with cefazolin, and 20.7% (n ϭ 12/58) were treated with oxacillin.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our results are consistent with those from other related recently published studies (12,16,17,27). However, in comparison to previous studies, we observed higher rates of endocarditis, in which 16.5% (17/103) of patients carrying the diagnosis of infectious endocarditis were treated with cefazolin, and 20.7% (n ϭ 12/58) were treated with oxacillin.…”
Section: Discussionsupporting
confidence: 72%
“…We did not detect differences in efficacy according to study center, and the inclusion of the study center in our multivariate models failed to significantly improve predictions of failure. Recent studies have observed higher discontinuation rates with semisynthetic penicillins than with cefazolin (17,27), which may partially explain the findings in our composite endpoint of slightly higher failure rates with oxacillin than with cefazolin. However, we did not detect significant differences in the adverse drug events between these agents.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The adjusted estimate was in the opposite direction (aOR, 1.2; 95% CI 0.3 to 4.5; P ϭ 0.76) but again with very wide uncertainty. A study by Li et al (15) found a statistically significant difference in the comparison of the raw proportions of failures in cefazolin and oxacillin groups, 24% versus 47% (P ϭ 0.04), but did not present a multivariate-adjusted effect size estimate or confidence interval, although choice of antimicrobial was not statistically significantly associated with treatment failure in a multivariate model (P ϭ 0.36). Paul et al also examined the association between receipt of cefazolin (compared to oxacillin) and death at 90 days (as measured by a national death registry) in MSSA BSI cases and found a reduction in the odds of death (aOR, 0.81) but a wide confidence interval (95% CI, 0.18 to 3.62) (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, several observation studies suggest treatment failure is not more common with cefazolin than with antistaphylococcal penicillins (15)(16)(17), and a recent large Canadian observational study found a substantial mortality reduction in those receiving cefazolin compared to those receiving cloxacillin (18), although this hazard reduction was not statistically significant (18). Thus, further data on the comparative outcomes for MSSA BSI treated by cefazolin or antistaphylococcal penicillins are needed to clarify whether either of these treatment options is superior.…”
mentioning
confidence: 99%